Arahan Pengembangan Zona Pelayanan Infrastruktur Air Limbah Domestik di Kecamatan Makassar, Kota Makassar - Asriani Asriani; Muh. Yamin Jinca; Yashinta Kumala Dewi Sutopo (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
The population growth that inhabits urban areas causes widespread outbreaks that trigger the increase in environmental pollution caused by wastewater. According to data obtained from the Slum Improvement Action Plan document of the Ministry of Public Works and Public Housing (2015), in Makassar City 7,684 houses did not have latrines. The profile of the Makassar City slum on the RP2KPKP document shows that 35,827 sewerage systems incorporated with drainage channels. This plan aims to assess the zone of the ideal domestic wastewater infrastructure services based on NSMP, evaluate its application in Makassar City, and formulate planning concepts that are in accordance with the existing problems. This research was conducted by synthesizing the literature review as a reference for determining research variables, criteria, and indicators; evaluating the zone of wastewater infrastructure services by scoring method; reviewing public perceptions using the Customer Satisfaction Index (CSI) method; and choosing the management system that will be applied with the system determination analysis method. The results of this study are in the form of literature synthesis, results of zoning analysis of wastewater infrastructure services in Makassar City in general, and in Makassar District specifically, as well as the direction of planning concepts at that location. This research is expected to be able to bring a healthier image of Makassar wastewater management to support the realization of Healthy City.